Self-Efficacy, Anxiety Level, and their Effects on Students’ Self-Persistence in Learning Science - Maryani, Ika; Cahyani, Hana Selvi Dwi; Ulfah, Amaliyah (Journal of Education Technology, 2024)
The current problem is that many prospective teachers have not been able to complete their studies at university. This is due to obstacles from within themselves or from the surrounding environment. This study analyzes self-efficacy, anxiety, self-persistence, and the relationship between self-efficacy and anxiety levels toward students' self-persistence in science learning. The research explores how self-efficacy and anxiety levels affect students' self-persistence to complete learning in all science courses to produce professional graduates. The study uses a quantitative approach, using the ex post facto method. The data collection technique uses a rating scale. The Likert scale of 56 valid statements successfully collected data on self-efficacy, anxiety levels, and self-persistence from 177 PGSD students. The data analysis technique in this study uses descriptive statistics followed by multiple linear regression to test the relationship between variables. The descriptive statistical analysis results show that students' self-efficacy and self-persistence in science learning are in the moderate category. Self-efficacy and anxiety levels towards students' self-persistence have a positive relationship. Furthermore, independent and dependent variables influence each other simultaneously and together. The percentage of relationships between variables is 91.2%, while other unknown factors influence the remaining 8.8%. The researcher recommends further study of other factors that may influence students' self-persistence in science learning.